Precise Temporal Responses in Whisker Trigeminal Neurons - Jones, Lauren M. (2004)
The ability of rats using their whiskers to perform fine tactile discrimination rivals that of humans using their fingertips. Rats must perform these discriminations rapidly and accurately while palpating the environment with their whiskers. This suggests that whisker-derived inputs produce a robust and reliable code, capable of capturing complex, high-frequency information. The first neural representation of whisker-derived stimulus information is in primary afferent neurons of the trigeminal ganglion. Here we demonstrate that there is a continuum of direction dependent response profiles in trigeminal neurons and provide the first quantitative analysis of the encoding of complex stimuli by these neurons. We show that all classes of trigeminal ganglion neurons respond with highly reproducible temporal spike patterns to transient stimuli. Such a robust coding mechanism may allow rapid perception of complex tactile features.